Early predictors of Guillain-Barré syndrome in the life course of women. (2nd September 2017) - Auger, Nathalie; Quach, Caroline; Healy-Profitós, Jessica; Dinh, Trish; Chassé, Michaël
Abstract: Background: We sought to determine if immune disorders early in life were associated with the later risk of Guillain-Barré syndrome, a neurological disorder thought to be infection-related. Methods: We conducted a longitudinal cohort study with 16 108 819 person-years of follow-up for a population of 1 108 541 parous women in Quebec, Canada (1989–2014). The outcome was Guillain-Barré syndrome. We identified women with potential risk factors for future Guillain-Barré syndrome, including immune-mediated and rheumatological diseases, cancer, transfusion, surgical procedures and pregnancy-specific disorders. We estimated hazard ratios (HR) and 95% confidence intervals (CI) for the association of risk factors with later onset of Guillain-Barré syndrome, adjusted for personal characteristics of women. Results: The overall incidence of Guillain-Barré syndrome was 1.42 per 100 000 person-years. Incidence was higher for women with immune-mediated (8.79 per 100 000 person-years) and rheumatological disorders (9.84 per 100 000 person-years), transfusion (4.41 per 100 000 person-years), and preeclampsia (2.62 per 100 000 person-years). Immune-mediated disorders were associated with six times the risk of Guillain-Barré syndrome (HR 6.57, 95% CI 3.58 to 12.04), rheumatological disorders with seven times the risk (HR 7.23, 95% CI 3.21 to 16.28), transfusion three times the risk (HR 3.58, 95% CI 1.83 to 6.98) and preeclampsia two times the risk (HR 2.01, 95% CI 1.29 to 3.12). Women with other potential risk factors did not have an increased risk of Guillain-Barré syndrome. Conclusions: Immune-related conditions that occur early in life are associated with an increased risk of Guillain-Barré syndrome. The pathophysiology of Guillain-Barré syndrome may extend beyond infectious triggers.